(untitled) (International Journal of Engineering and Computer Science, 2017)
Testing automation tools enables developers and testers to effortlessly computerize the complete practice of difficult in software progress. The intention of this research paper is to carry out a comparing and studying the concepts, builds and features of automated tools such as the Ranorex and the Automated QA TestComplete based on criteria such as the hard work involved with generating test scripts, capacity to playback the scripts, end result reports, and expenditure. The elementary objective is to investigate the features and concepts supported by these two functional testing tools in order to access unconventionally what pros and cons of the tools and what could be the guidelines for its additional expansion